Extreme premaxillary protrusion in the king‐of‐the‐salmon, Trachipterus altivelis. (22nd October 2019) - Ferry, Lara A.; Paig‐Tran, Erin W.; Summers, Adam P.; Liem, Karel F.
Abstract: The king‐of‐the‐salmon, Trachipterus altivelis (Lampriformes), has an unusual set of oral jaws which allow it the ability to protrude the entire upper jaw, containing the premaxilla and the maxilla bones, to extreme distances. Here, we provide a short description of the cranial anatomy and mechanism of jaw protrusion in T. altivelis using hand‐drawn illustrations (by KF), supplemented by CT‐scans. We then place the protrusion abilities of T. altivelis into context by comparing anatomical jaw protrusion with protrusion from other members of the Lampriformes, other unrelated species with highly protrusile jaws, and unrelated species with more stereotypical amounts of jaw protrusion. Through these comparisons we demonstrate that T. altivelis is indeed, capable of some of the most extreme premaxillary protrusion as of yet discovered, even when taking into account the extreme morphological modifications that facilitate said protrusion. That is to say, T. altivelis can protrude the premaxilla farther than one would predict from the length of the ascending process alone. Abstract : Anatomy of T. altivelis revealed via CT imaging. The center panel shows the entire specimen. The white box denotes the cranial region, which is enlarged in the top and bottom panels. Above is the lateral view, and below is the ventral view.